Implementasi Metode Bernyanyi dalam Pengembangan Keterampilan Berbahasa Arab di TK Kemuning - Naely Kamilatul Azizah; Iin Herniati; Tri Miyani (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Arabic is an international language that is closely related to Islam and is used in various countries in the world. Arabic is also referred to as the language of the Qur'an because the Qur'an is written in Arabic. According to the Big Indonesian Dictionary (KBBI) Arabic is defined as "the name of a nation in the Arabian Peninsula and the Middle East." Meanwhile, according to Al-Ghalayin, Arabic is the sentences used by Arabs to express their goals (thoughts and feelings). This research method uses qualitative methods. This was chosen because this study aims to clearly reveal the implementation of the singing method in the development of Arabic language skills in Kemuning Kindergarten. Learning Arabic can be done in various ways and methods. Therefore, learning of vocabulary (al-mufradat) is an important element in Arabic because an adequate Arabic vocabulary can support a person in communicating and writing in that language. As a learning method, singing is more of a play activity than a learning activity itself. In addition to entertaining, singing can eliminate boredom and strengthen children's understanding of the material being taught. Mufradat learning is the most basic thing that must be mastered by someone in learning Arabic which is considered a foreign language by students. Once the importance of the mufradat aspect in learning foreign languages, it is necessary to use specific methods and strategies in learning so that the learning outcomes can be achieved as expected. Keywords: Arabic Language, Research Methods